Chronic pruritus in atopic dermatitis – mechanisms and different ways of treatment, affect on quality of life - Ostaszewska, Sandra; Morawski, Przemysław; Augustynowicz, Kinga; Popińska, Zuzanna; Chrzanowski, Jakub; Szymańska, Ewa; Łoginoff, Jan; Świąder, Kinga; Pactwa, Filip (Journal of Education, Health and Sport, 2023)
Introduction: Pruritus in atopic dermatitis is one of the main symptoms of the disease and the one that causes a significant impact on quality of life. It is important to control itching because it’s not only an unplesant sense. Scratching topically deepen the dermatitis, damages the epidermal barrier causing additional infections possible and makes it harder to acheive a remission of the disease. It is also highly associated with stress and has an impact on mental health of the patient. In this article we present a summary of how pruritus affects the quality of life, mechanisms of pruritus and possible treatment. Materials and methods: Our work is based on the articles published in PubMed, medical books and websites. We were looking for the key words such as ‘stress and itch’, ‘pruritus treatment’, ‘chronic itch in atopic dermatitis’, ‘itch and quality of life’. Results: Patients with atopic dermatitis should come under miltidisciplinar treatment to acheive the best possible control of symptoms. This will result in higher quality of life and better mental health of the patient. Conclusions: There is a high need to develop new targeted medications as contemporary medicine knows a lot more about the mechanism of pruritus. Many new types of treatment are being studied and soon we may have more options to choose in systemic and topical therapy. We should also concetrate more on a mental side of the disease.